Russian Federation - Export Diversification through Competition and Innovation : A Policy Agenda - World Bank (Washington, DC, 2013)
Russia's exports became further dominated by petroleum and natural gas over the last decade. The sector experienced double-digit annual export growth in the last decade and represented almost 65 percent of Russia's exports value in 2009 a product of higher commodity prices and higher export volumes. Export growth rates of the non-oil and gas sector were also notable. Such industries as machinery, electronics, transportation equipment and chemicals reached a combined growth rate in export value of 10 percent in the last decade. This more positive comparison, however, hides relevant structural limitations in Russia's trade performance. Moreover, Russia's revealed comparative advantage seems concentrated in the 'periphery' of the product-space map, which may limit the potential for export diversification. This includes industries such as raw materials (26 products) and forestry (11 products) out of a total of 97 identified products. (At the center of the product-space are industries such as metallurgy, vehicles, machinery, etc, in which Russia does not show comparative advantages). Such specialization is sometimes considered problematic because the capabilities developed in those sectors are not easily redeployed to other industries, hindering the process of economic diversification. Yet, several resource-rich countries have managed to expand their comparative advantages beyond the traditional, natural resource-intensive products. Russian firms are, on average, larger than the average firm in the ECA region but too few firms export. It is a well documented fact that only a minority of firms in an economy export. Economic modernization and export diversification are priorities in the Russian economic policy agenda, with several measures being undertaken in recent years to promote growth in the non-oil and gas sectors. Yet the reason why some firms succeed in breaking into foreign markets while others do not is far from fully understood. In this note, the author tries to identify the binding constraints to export diversification in Russia. Using firm-level data, the author identify which investment climate factors are affecting Russian firm's propensity of engaging in export activities. Results show that lack of competition and entrepreneurial innovation are relevant obstacles to the emergence of new, potentially exportable products.